2016
DOI: 10.3109/03009742.2016.1153141
|View full text |Cite
|
Sign up to set email alerts
|

Lung and gastrointestinal complications are leading causes of death in SCORE, a multi-ethnic Singapore systemic sclerosis cohort

Abstract: PAH, ILD, and GI complications were leading causes of death in this cohort. We identified a high-risk group of patients who would benefit from closer monitoring and early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
0
33
1
Order By: Relevance
“…In CSRG, upper gastrointestinal involvement was associated with mortality but not PAH and ILD, possibly due to less sensitive means of identifying the latter complications. Although mortality was highest in SCORE, there were no independent risk predictors of mortality in this analysis, although overlap syndrome and systolic pulmonary arterial pressure (sPAP) greater than 40 mmHg have been shown previously to predict mortality in this cohort (13). Also in contrast to the other cohorts (38), survival in lcSSc was relatively short in SCORE, especially in incident patients.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…In CSRG, upper gastrointestinal involvement was associated with mortality but not PAH and ILD, possibly due to less sensitive means of identifying the latter complications. Although mortality was highest in SCORE, there were no independent risk predictors of mortality in this analysis, although overlap syndrome and systolic pulmonary arterial pressure (sPAP) greater than 40 mmHg have been shown previously to predict mortality in this cohort (13). Also in contrast to the other cohorts (38), survival in lcSSc was relatively short in SCORE, especially in incident patients.…”
Section: Discussioncontrasting
confidence: 59%
“…Additional risk factors for mortality included older age at disease onset, high mRSS, low DLCOc, ILD and PAH. Cardiopulmonary complications such as PAH and ILD, were responsible for the majority of deaths (13, 18). Malignancy was more common in the older cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further supporting the strong association between severe GI involvement and mortality across SSc subtypes and geographic areas, a study of a large SSc cohort (N = 349) from Singapore found that the use of parenteral nutrition was also a strong independent predictor of mortality. 18 GI involvement remains one of the leading causes of deaths related to SSc over decades. 7,16 Primary causes of death for SSc patients observed during a 30-year time were evaluated in 2007.…”
Section: Effects Of Gi Involvement On Mortality In Sscmentioning
confidence: 99%
“…Gastrointestinal involvement in SSc is associated with significant morbidity, mortality, and impact on health-related quality of life [ 7 ]. In a well-characterised local multiethnic systemic sclerosis cohort Singapore (SCORE) where patients fulfilled the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) or Very Early Diagnosis of Systemic Sclerosis (VEDOSS) criteria, 57% of deaths were attributed to SSc, with pulmonary arterial hypertension (PAH), interstitial lung disease (ILD), and gastrointestinal (GI) complications as the leading causes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%